Digital health services as part of care processes - Koivuluoma, Minna; Haverinen, Jari; Reponen, Jarmo (Finnish Journal of eHealth and eWelfare, 2022)
Finland aims to be a pioneer in digitalization by reforming the processes of public services and digitalizing services. In healthcare, the introduction of digital transaction services is aimed at bettering health care services and cost benefits. The use of digital transaction services in recent years has increased, but the realization of digitalization is still low. One of the challenges in increasing the use of digital transaction services is the non-renewable state of the care processes. In order to improve digital services in Southern Ostrobothnia, this study aimed to find out how healthcare processes are taken into account in the development of digital services in Southern Ostrobothnia. In order to achieve this goal, studies were performed to find out what kind of digital services are being used and developed in healthcare, the prevalence of these digital services, how the consortium of e-services and health care processes is being developed, how the development of e-services is being carried out, and what the effects of the Covid-19 pandemic are on e-services in healthcare. The basis of the study is described in a literature review, in which information was sought on digital health services in the Nordic countries. Information on the consideration of health care processes in the development of digital transaction services was collected from interviews with health care and information management professionals. There are several different electronic transaction services in healthcare, which need to be developed for the possibility of a smoother transaction experience. In deploying digital services, care processes will be modified, but these processes are not being redesigned to ensure that the benefits of the digital services can be achieved. It was desired that the development of digital transaction services would be advanced and to include process planning more firmly in the development process. There are good preconditions for formulating electronic transaction services and processes into a unified whole. In the future, it will be important to define the benefit of goals for digital services and to craft a strategy to achieve them. The benefits of digital transaction services materialize when defined processes are digitalized in such a way that they are part of working practices and citizens' transactions.